Hemos cambiado : educacion, conquistas y deseos de las ninas en el siglo XIX - Lopez, Oresta; Monroy, Manuel (Mexico, D.F. : Castillo, 2006)
Describes the history of women in Mexico during the 19th century including their legal rights and their aspirations.
Includes bibliographical references (p. 58-59).
Keywords: Women's rights -- Mexico -- History -- 19th century -- Juvenile literature; Women -- Mexico -- Social life and customs -- 19th century -- Juvenile literature; Women -- Education -- Mexico -- History -- 19th century -- Juvenile literature; Mujeres -- Derechos -- Mexico -- Historia -- Siglo XIX -- Literatura juvenil; Mujeres -- Mexico -- Vida social y costumbres -- Siglo XIX -- Literatura juvenil; Mujeres -- Educacion -- Mexico -- Historia -- Siglo XIX -- Literatura juvenil